2021
DOI: 10.1152/japplphysiol.01039.2020
|View full text |Cite
|
Sign up to set email alerts
|

Collapsibility of caval vessels and right ventricular afterload: decoupling of stroke volume variation from preload during mechanical ventilation

Abstract: Background: Collapsibility of caval vessels and stroke volume and pulse pressure variations (SVV, PPV) are used as indicators of volume responsiveness. Their behavior under increasing airway pressures and changing right ventricular afterload is incompletely understood. If the phenomena of SVV and PPV augmentation are manifestations of decreasing preload, they should be accompanied by decreasing transmural right atrial pressures. Methods: Eight healthy pigs equipped with ultrasonic flow probes on the pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Studies have shown that SVV is significantly correlated with blood volume, and can accurately reflect the volume status of individuals and responsiveness to fluid therapy [ 15 ]. In spinal surgery, SVV can accurately predict fluid responsiveness during prone position surgery [ 16 , 17 ]. In this study, although an equal volume of colloidal solution was supplemented after ANH, the ANH group presented a significant decrease in MAP immediately after hemodilution and an increase in SVV%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SVV is significantly correlated with blood volume, and can accurately reflect the volume status of individuals and responsiveness to fluid therapy [ 15 ]. In spinal surgery, SVV can accurately predict fluid responsiveness during prone position surgery [ 16 , 17 ]. In this study, although an equal volume of colloidal solution was supplemented after ANH, the ANH group presented a significant decrease in MAP immediately after hemodilution and an increase in SVV%.…”
Section: Discussionmentioning
confidence: 99%
“…The reality of this theoretical limitation is not certain, as it was evaluated by only one human study with many limitations [ 61 ]. A recent study in pigs suggests that elevation in the level of PEEP and the accompanying increase in right ventricular afterload increase PPV independently of variations in preload [ 62 ]. However, the animals in this study did not have right ventricular failure [ 62 ].…”
Section: Pulse Pressure and Stroke Volume Variationsmentioning
confidence: 99%
“…A recent study in pigs suggests that elevation in the level of PEEP and the accompanying increase in right ventricular afterload increase PPV independently of variations in preload [ 62 ]. However, the animals in this study did not have right ventricular failure [ 62 ]. Despite these limitations, recent studies have shown that the relative changes in PPV and SVV may help assess fluid responsiveness, even in cases where its absolute value is not interpretable.…”
Section: Pulse Pressure and Stroke Volume Variationsmentioning
confidence: 99%
“…Therefore, RV failure and pulmonary hypertension render PPV invalid for the prediction of volume responsiveness ( Daudel et al, 2010 ; Wyler von Ballmoos et al, 2010 ). In such context, PPV and related techniques may rather reflect an afterload-dependency of the RV ( Vieillard-Baron et al, 1999 ; Vieillard-Baron et al, 2015 ; Valenti et al, 2021 ). Several pulmonary factors like compliance ( Robotham et al, 1983 ; de Waal et al, 2009 ; Mesquida et al, 2011 ), respiratory rate, tidal volume ( De Backer et al, 2005 ; De Backer et al, 2009 ; Slobod et al, 2022 ), and airway driving pressure ( Muller et al, 2010 ) influence PPV, as will circulatory factors like the need for a sinus rhythm and aortic elastance and thus ventricular-aortic coupling ( Magder, 2010 ; Sondergaard, 2013 ).…”
Section: Monitoring Of Arterial and Central Venous Pressure Swingsmentioning
confidence: 99%
“…Even though use of the pulmonary artery catheter (PAC) has declined over the last decades after a series of negative clinical trials ( Parker et al, 2023 ), it remains a cornerstone for complex hemodynamic monitoring and is still recommended for situations with impending right heart failure and for patients unresponsive to initial treatment ( Vieillard-Baron et al, 2016 ). As increases in RV afterload are common in pulmonary diseases and may exacerbate heart-lung interactions ( Vieillard-Baron et al, 1999 ; Schmitt et al, 2001 ; Vieillard-Baron and Jardin, 2003 ; Repessé et al, 2016 ; Valenti et al, 2021 ), the PAC’s ability to monitor RV dysfunction with an increased ratio of CVP to pulmonary artery occlusion pressure is helpful ( Monchi et al, 1998 ; Osman et al, 2009 ). Additionally, since disturbed gas exchange may contribute to hypoxic pulmonary vasoconstriction - often presenting as an increased transpulmonary pressure gradient ( Bull et al, 2010 ) and an increased isovolumetric contraction pressure in pulmonary artery pressure tracings ( Jardin et al, 1987 ; Jardin et al, 1989 ; Berger et al, 2014 ; Slobod et al, 2022 ) - the continuous assessment of mixed venous oxygenation can help assess the extent of vasoconstriction and shunt, and the contribution of venous admixture to oxygenation disorders ( Takala, 2007 ; Bootsma et al, 2022 ).…”
Section: Advanced Bedside Techniques: Pulmonary Artery Catheterizatio...mentioning
confidence: 99%